Two species of Lumbricillus (Enchytraeidae, Annelida) new to Antarctica - Lee, Jeounghee; Klinth, Mårten J; Jung, Jongwoo (Polar Research, 2019)
The intertidal fauna of the Antarctic Peninsula has a relatively high species diversity, due to its warmer environment compared to other parts of Antarctica. Marine oligochaetes are, in general, one of the most diverse and ecologically important benthic organism groups, at least in the littoral zone. Antarctica has been one of the least studied areas with regard to oligochaete diversity. Here we report two Lumbricillus species (Lumbricillus antarcticus Stephenson, 1932 and Lumbricillus sejongensis sp. nov.) new to Antarctica, found in a tidal pool on the Barton Peninsula, King George Island. The diversity of this genus remains poorly known for Antarctica and the Subantarctic islands, and what we know is based on a few patchy studies.
Keywords: Sørishavet; belteormer; bentiske organismer; biodiversitet; fauna; marin biologi; tidevann

A preliminary survey of the terrestrial arthropods of the Rosenthal Islands, Antarctica - Gantz, J D; Spacht, Drew E; Lee, Richard E (Polar Research, 2018)
The Rosenthal Islands lie along the western edge of the Antarctic Peninsula. They are largely inaccessible and the few research projects in the area have focused on seabird colonies, so nothing has been known about the arthropod fauna on these islands. We conducted a preliminary survey of the arthropods associated with large penguin colonies. We identified two species of Collembola (Cryptopygus antarcticus and Friesea grisea), four species of mites (Alaskozetes antarcticus, Hydrogamasellus racovitzai, Tectopenthalodes villosus and Rhagidia sp.) and one insect (Belgica antarctica). The mite A. antarcticus and the collembolan C. antarcticus were common in large aggregations at our collecting sites and were occasionally observed on the surface of penguin guano without vegetative cover. The insect, a chironomid midge, was less common and found only in vegetated areas.
Keywords: Antarktis; biologi; fauna; leddyr; midder; pingviner; zoologi

Ontogenetic changes in the feeding strategy of Lepidonotothen nudifrons (Pisces, Nototheniidae) off the South Shetland Islands and the Antarctic Peninsula - Blasina, Gabriela; Cazorla, Andrea Lopez; Antoni, Mariana Deli; Bruno, Daniel; Delpiani, Matías; Díaz de Astarloa, Juan Martín (Polar Research, 2017)
The diet and feeding strategy of Lepidonotothen nudifrons off the South Shetland Islands and the Antarctic Peninsula, as well as their variation in relation to ontogenetic stage (juvenile– adult) and sampling area, were determined by stomach contents analysis. Additionally, the trophic level of this species was estimated to determine its position within the Antarctic food web. Out of 247 specimens with prey in their stomachs, 144 were caught near the South Shetland Islands and 103 off the Antarctic Peninsula. Ontogenetic changes in the trophic ecology of L. nudifrons were observed in both areas and were mainly related to a decrease of copepods and an increase of euphausiids in the diet. The diet of juveniles from the South Shetland Islands was characterized by the dominance of calanoid copepods, followed by isopods and amphipods, whereas diet off the Antarctic Peninsula was dominated by amphipods and cyclopoid copepods. The diet in adults was dominated by amphipods and euphausiids in both areas. The specialization of individual predators on different prey types was observed when considering the whole population of L. nudifrons, but when ontogenetic stages were considered separately it showed a more mixed feeding strategy, with different dominant prey for each class. Although the trophic level increased with fish size, L. nudifrons can be classified as secondary consumer throughout its lifespan.
Keywords: Sørishavet; amfipoder; copepoder; euphausiacea; fauna; fisker; isopoder; marin zoologi; økosystemer

Potential chemical defenses of Antarctic benthic organisms against marine bacteria - Sacristán-Soriano, Oriol; Angulo-Preckler, Carlos; Vázquez, Jennifer; Avila, Conxita (Polar Research, 2017)
The continental shelf of Antarctica harbours rich suspension-feeding macroinvertebrate communities that are continuously exposed to large populations of free-living microbes. To avoid settlement or fouling by undesirable microorganisms that could cause infection or collapse filter-feeding systems, these macroinvertebrates might regulate the epibiotic microbial mat through chemical interactions. In Antarctic chemical ecology, the antibacterial roles of natural products remain mostly unknown. A necessary first step is to identify organisms that produce compounds with potential ecological relevance. For that reason, we tested the crude organic extracts of 116 taxa of Antarctic benthic organisms for antibacterial activity against a panel of seven strains of marine bacteria. Nine out of 11 phyla tested had antibacterial properties. However, inhibitory activity was quite selective and species-specific. These patterns suggest that Antarctic benthic organisms may produce diverse bioactive metabolites with different antibacterial activities or, alternatively, those contrasting profiles may be shaped by environmental and biological interactions acting at a small spatial scale. The reasons of such selectivity remain to be further investigated and may contribute to the identification of bioactive compounds with pharmaceutical applications.
Keywords: Sørishavet; alger; biodiversitet; biologi; fauna; kjemisk; kontinentalsokkel; makrovirvelløse dyr; mikrober; mikroorganismer; økologi

Antarktis - kort fortalt - Balto, Ann Kristin; Hallanger, Ingeborg Gammelsæter; Jenssen, Elin Vinje (Norsk polarinstitutt, 2015)
Keywords: Antarktis; biologi; fauna; flora; historie; klima; miljø; natureklima; naturhistorie